Understanding Acute Respiratory Illness in Nepalese Children Under Five: Insights From the 2016 Nepal Demographic and Health Survey (Journal of Health Promotion, 2025)
Acute Respiratory Illness (ARI) remains a critical public health challenge for children under five in Nepal, with persistent socioeconomic inequities in disease burden. This cross-sectional study analyzed Nepal’s 2016 Demographic and Health Survey (NDHS) (n = 4,887) to identify determinants of ARI using caregiver-reported symptoms of rapid breathing and chest-related issues within two weeks of the survey. Weighted logistic regression analyses examined associations between ARI and variables such as wealth quintile, residence type, maternal education, and child age. Nationally, ARI prevalence stood at 2.41%, with pronounced disparities: children from the poorest wealth quintile were 5.6 times more likely to have ARI than the richest (3.32% vs 0.59%), while Province 6 reported the highest regional burden (3.37%). Multivariate analysis confirmed household wealth as the significant predictor (AOR = 1.60, 95% CI: 0.063–40.836), though wide confidence intervals indicated model overdispersion. Notably, 84.92% of children with ARI received healthcare through the help of their caregivers, with the majority seeking services from private facilities (32.30%) and privately owned pharmacies (27.92%), highlighting limited utilization of public sector services. These findings reveal wealth-based health disparities despite Nepal’s progress toward Sustainable Development Goal (SDG) child mortality targets. The results advocate for province-specific interventions in high-burden regions like Karnali, including mobile pneumonia clinics and biomass fuel transition programs. Socioeconomic disparities play a key role in ARI prevalence among children under five in Nepal. Interventions aimed at reducing care-seeking fragmentation while targeting poverty-alleviation strategies to reduce ARI’s impact on marginalized populations could be beneficial. Future research should aim to identify additional risk factors that were not explored in the NDHS survey.